2018
DOI: 10.18785/ojhe.1401.07
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Dilemmas Experienced by Australian Rehabilitation Counsellors

Abstract: Private sector rehabilitation counsellors operate in a dynamic and complex environment in which their decisions are influenced by several stakeholder interests including workers' compensation authority regulators, scheme appointed agents, employers, and injured workers. The potentially competing interests of all parties often challenge the values and professional responsibilities of rehabilitation counsellors. The current study aimed to address the gap identified in the literature concerning ethical dilemmas u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…İkiz, Sensoy et al ( 2017) observed that school counsellors received support from supervision groups, colleagues, written sources, attorneys and prosecutors, institution managers, and police in cases where they experienced ethical dilemmas. In another study, McLennan, Ryan, and Randall (2018) determined that school counsellors prefer personal judgments and to discuss isses with colleagues and managers rather than consider ethical codes in overcoming ethical dilemmas. Hinkeldey and Spokane (1985) found that school counsellors did not trust the legal system when deciding what to do in an ethical dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…İkiz, Sensoy et al ( 2017) observed that school counsellors received support from supervision groups, colleagues, written sources, attorneys and prosecutors, institution managers, and police in cases where they experienced ethical dilemmas. In another study, McLennan, Ryan, and Randall (2018) determined that school counsellors prefer personal judgments and to discuss isses with colleagues and managers rather than consider ethical codes in overcoming ethical dilemmas. Hinkeldey and Spokane (1985) found that school counsellors did not trust the legal system when deciding what to do in an ethical dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Corey et al 15 Model includes eight steps to experience ethical issue, which is an effective tool to challenge ethical dilemma, and widely used to help practitioners making ethical decisions. 16 Patients are vulnerable people in vulnerable situations. Nurses, as professional and moral agents, have a responsibility for upholding specific standards during closely contacting with them according to the Code of Professional Conduct and Ethics for Registered Nurses and Registered Midwives.…”
Section: Ethic Issues and Analysismentioning
confidence: 99%